FERMENTATION QUALITY OF KING GRASS SILAGE TREATED WITH LIQUID OR DRIED INOCULANT OF LACTIC ACID BACTERIA - Santoso, B.; Hariadi, B. Tj.; Jeni, J. (Diponegoro University, 2015)
The aim of this study was to evaluate the nutritive value and fermentation characteristic of king grass silage treated with addition of liquid or dried lactic acid bacteria (LAB) inoculant. Experiment was arranged to a completely randomized design with four treatments and three replications. Four treatments as follows (A) king grass without LAB inoculant as the control; (B) king grass + 30 ml of liquid of epiphytic LAB inoculant/kg of fresh forage; (C) king grass + 30 g of freeze-dried powder of LAB inoculant/kg of fresh forage; (D) king grass + 30 g of centrifuged powder of LAB inoculant/kg of fresh forage. The liquid LAB inoculant was sprayed on the top of grass and then mannualy mixed by hand. The intial LAB concentration in all inoculants were 1.0 × 106 cfu/g. About 500 g of silage materials were ensiled into plastic silos and stored at room temperatures (approximately 28oC) for 30 days. Results showed that pH value, concentrations of lactic acid, N-amonia (NH3-N), butyric acid and total volatile fatty acids (VFA) as well as Fleigh Point were affected by treatment of LAB inoculant. Silage treated with liquid or dried of LAB inoculant had lower (P